The role of profitability and thin capitalization in shaping tax avoidance behavior among IDX-listed mining companies - Nindia Innekeputri; Sufiyati Sufiyati (WIM Solusi Prima, 2026)
Corporate tax avoidance is a significant issue because it has a direct impact on government revenue and reflects how companies manage their tax responsibilities. In Indonesia, this issue is especially important as tax revenue serves as a key source of funding for public spending and national development. Therefore, examining tax avoidance is important to understand the factors that encourage companies to minimize their tax burdens. This study examines whether profitability and thin capitalization affect tax avoidance in mining-sector companies listed on the Indonesia Stock Exchange during 2021–2024. The study uses secondary data from annual financial statements and applies purposive sampling. After the sample-selection process, 12 companies met the research criteria, producing 48 firm-year observations. The data are analyzed using pooled multiple linear regression based on the statistical procedure using IBM SPSS Statistics 31. The results show that profitability has a negative and significant coefficient on the tax avoidance, while thin capitalization has a positive but insignificant coefficient on tax avoidance. These findings imply that companies with higher profitability tend to be more compliant in fulfilling their tax obligations, while the use of debt has not significantly encouraged tax avoidance practices in the observed mining-sector companies. The results of this study are expected to provide insights for regulators in strengthening tax supervision, for investors in assessing corporate tax behavior, and for companies in formulating tax strategies that remain aligned with applicable regulations.